The Importance of Parents In Developing Young Children’s Language Skills Through The Use of Digital Storytelling - Syifa Azzah Hafidhoh; Nur Arifah Drajati; Fatma Sukmawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
The role of parents in educating children has a significant influence on their development, including the language skills in early childhood that can be improved through storytelling methods, including digital storytelling. The aim of this study was to find out how parents in one of the preschools in East Java were involved in promoting early childhood language skills using digital storytelling. This study employed a case study with a qualitative descriptive approach. The data was collected through observation, and interviews. Data analysis using source triangulation. The five parents of the students served as sources for the study data. The results of this study showed that the involvement of parents in the preschool in East Java as partner teachers, friends, and facilitators was adequate for children’s language skills to grow and develop. Parents took an active role in fostering their child’s language development. Digital Storytelling can increase children’s language abilities and allow them to think logically, methodically, critically, and creatively. The findings suggest that digital storytellingcan bean effective method for developing language skills in young children. Educators and practitioners in early childhood education can consider incorporating digital storytelling techniques into their curriculum and teaching practices to enhance language learning outcomes.